Epidemiological survey of hepatitis C in a region considered to have high prevalence: the state of Minas Gerais, Brazil - Gomide,Geisa Perez Medina (2019)
Abstract INTRODUCTION: The prevalence of hepatitis C virus (HCV) infection is affected by demographic, virological, clinical, and lifestyle-related factors and varies in different regions in Brazil or worldwide. The present study aimed to clarify the epidemiological patterns of HCV infection in the interior region of Brazil. METHODS: This study was conducted in the Southern Triangle Macro-region of the state of Minas Gerais, Brazil, according to the guidelines of the National Program for the Prevention and Control of Viral Hepatitis. The participants answered a structured questionnaire on social and epidemiological factors. Immunochromatographic rapid tests were used for the qualitative detection of antibodies against HCV in whole blood (Alere HCV® Code 02FK10) in adult subjects by a free-standing method. RESULTS: Of 24,085 tested individuals, 184 (0.76%) were anti-HCV positive. The majority of anti-HCV-positive individuals were born between 1951 and 1980 (n=146 [79.3%]), with 68 women and 116 men. Identified risk factors included syringe and/or needle sharing (p = 0.003), being in prison (p = 0.004), and having tattoos or piercings (p = 0.005) and were significantly associated with the decade of birth. CONCLUSIONS: The study shows the importance of testing populations at risk for HCV infection, including incarcerated individuals, those with tattoos or piercings, those who share or have shared syringes or needles, and those in high-risk birth cohorts (1950s, 1960s, and 1970s) in the Southern Triangle Macro-region.